If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8(x + 2) = -3x + -31 Reorder the terms: -8(2 + x) = -3x + -31 (2 * -8 + x * -8) = -3x + -31 (-16 + -8x) = -3x + -31 Reorder the terms: -16 + -8x = -31 + -3x Solving -16 + -8x = -31 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. -16 + -8x + 3x = -31 + -3x + 3x Combine like terms: -8x + 3x = -5x -16 + -5x = -31 + -3x + 3x Combine like terms: -3x + 3x = 0 -16 + -5x = -31 + 0 -16 + -5x = -31 Add '16' to each side of the equation. -16 + 16 + -5x = -31 + 16 Combine like terms: -16 + 16 = 0 0 + -5x = -31 + 16 -5x = -31 + 16 Combine like terms: -31 + 16 = -15 -5x = -15 Divide each side by '-5'. x = 3 Simplifying x = 3
| -1/2-7=_ | | 2/8k=16/24 | | 6y-10+6y+10= | | -6g+8=-4g | | 5x-8=6x+15 | | -5t^2-8t=-120 | | -3b+4b=14-b | | 10x+-5=3x+9 | | 13=-3n+11-n | | 1/12x=3 | | 7(5x+3)=371 | | 72=-8u | | 1/2(8x-6)=9 | | 6(5x+7)=102 | | -13=y/2 | | k-9.1=4 | | y-4=2.5(x+12) | | -2xy+-7y= | | 7(6x+7)=49 | | 0.75x+0.5=-0.0625x+0.375 | | 123fu=jop+585+55 | | 4y-16=3y+5 | | 0.5x+70t=2x | | 600(.8)+x=700 | | 15x+22=150 | | 5-2/3x=1/2x-4 | | 7p=-8u | | 4e^1(x^2+1)=0 | | 700+x(.4)=720 | | s(t)=t^2-4/t | | 1200+3x=2100 | | 1250=1/4q |